PEMENUHAN KEBUTUHAN SPIRITUAL BERHUBUNGAN DENGAN STATUS KECEMASAN MENGHADAPI MASA PENSIUN PADA PEGAWAI NEGERI SIPIL - Evi Nugraheni; Sarka Ade Susana; Fajriyati Nur Azizah (MEDIA ILMU KESEHATAN, 2014)
Background: All employees of the company or government employees will in time retire. Upon entering the age of 56 years, the employee or civil servant to retire. Retirement is a stage of life characterized by the presence of transition and change in psychosocial role that causes stress. Retirement impact on the physical, social and spiritual individual. Physical disorders includes activity inhibited activity. Social problems cause individuals less participate in social activities. Less of spiritual needs fulfillment are more likely to cause the individual less activity in religious. Objective: To identify the correlation between spiritual fulfillment and civil servants retirement anxiety in Sleman. Methods: This study was a cross cectional design study. Statistical tests using correlation Kendal Tau with significance level p=0.05. Samples were taken using simple random sampling involved 55 respondents. The research instrument used questionnaires spiritual needs and anxiety questionnaires. Results: The results showed that the civils servant unmet spiritual needs (98.2%) and 68.4% retirement in the category of moderate anxiety. Kendal Tau test showed p=0.042, indicating there was a relationship between the spiritual fulfillment with retirement anxiety indicating on civil servant with r=-0.274 showed weak relationship. Conclusion:Civil servant who had fulfilled spiritual needs would have moderate to mild levels of anxiety. Keywords: Spiritual Fulfillment, Anxiety, Retirement